The Influence of Human Resource Performance Evaluation on The Successful Work Performance - Berkat Krisman Zamasi; Eliyunus Waruwu; Eduar Baene; Maria Magdalena Batee (Yayasan Riset dan Pengembangan Intelektual, 2024)
This research aims to determine the effect of human resource performance evaluation on the performance success of BASARNAS in the Nias Islands. A quantitative approach was applied to prove the theory's truth scientifically and empirically, which refers to research principles; thus, the results obtained can be justified. The research instrument used was a questionnaire with a total of 30 statement items (15 statement items for each X and Y variable. From the Validity Test and Reliability Test, the research instruments used were regarded as valid and reliable, meaning that the questionnaire which has been distributed suits well as a research instrument. The sample in this study was 70 employees. Data was processed using the SPSS 2.0 Application. Results demonstrate that the value of R Square is 0.786. In other words, HR Work Evaluation influences Basarnas Nias Islands's performance success by 78.6%. This means that HR Work Evaluation significantly affects the performance success of BASARNAS in the Nias Islands.